Influence of soil environment on mortality of lentil due to soil borne pathogens - M.N. KHARE, D.R. SAXENA and (Indian Phytopathology, 2002)
Lentil suffers due to Fusarium oxysporum f. sp. lentis, Sclerotium rolfsii and Rhizoctonia bataticola causing vascular wilt, collar rot and root rot respectively. Total mortality of lentil increased in different combinations of these pathogens. Soil type, pH, temperature and moisture influenced quantum of pathogen and disease incidence. Sandy loam soils at 8.5 pH and 25Â°C are most condusive for all the three pathogens, individually as well as in combinations. Total mortality of lentil due to R. bataticola and its association with F. oxysporum f. sp. lentis was maximum at 30Â°C. F. oxysporum f. sp. lentis alone and in combination with S. rolfsii and R. bataticola caused maximum mortality at 30 per cent soil moisture. Mortality due to S. rolfsii was maximum at 25 per cent soil moisture.